Detection and identification of public health important pathogens present in fruit salads sold on Lagos State University campus: Article Retracted by the Authors - Ogunware, Adedayo Emmanuel; Esther, Odubiyi Opeyemi; Adedigba, Pelumi Abimbola; Adekoya, Adesewa Adeyinka (Journal of Experimental Sciences, 2020)
A total of fifteen pre-packaged fruit salad samples containing pineapple, water melon, pawpaw and cucumber sold in the Lagos State University, Ojo Campus was analyzed using culture techniques for its microbial qualities. Five bacteria genera isolates obtained are Bacillus spp, Staphylococcus aureus, Pseudomonas spp, Escherichia coli, Streptococcus and the three fungi genera isolates are Aspergillus species, Penicillium species, and Saccharomyces cerevisiae. Escherichia coli had the highest frequency of (40%) followed by Streptococcus with (20%), Staphylococcus, Bacillus, Pseudomonas has the same frequency of (13%). The total viable count was in the range of 1.6 × 105 cfu/g to 5.65 × 105 cfu/g while the total coliform count ranged from 1.0 × 105 to 3.3 × 105 cfu/g. The fungal count ranged from 1.5 × 105 to 3.4 × 105 cfu/g. This study revealed that fruit salads in the studied area needs proper sanitation practice during processing in order to avoid risks associated with the consumption of contaminated fruits for the consumers.